Living theory : the application of classical social theory to contemporary life - Hurst, Charles E. (Routledge, 2015)
Living Theory: The Application of Classical Social Theory to Contemporary Life, 2nd edition analyzes major features of modern society from the classical theory point of view, and suggests how modern life might be explained from this viewpoint. The author examines the works of four classical figures - Marx, Durkheim, Simmel, and Weber - because of their continuing influence on social theory, and because they addressed many of the central issues we confront in modern society. Topics new to this edition include: New electronic technologies The battle over valued property The role of trust in society Governmental secrecy Trafficking in human organs.